Use of Modified Technology Acceptance Models to E-business for MSMEs - Yusuf, Syahrial; Hadining, Aulia Fashanah (TALENTA Publisher, 2021)
Many MSMEs in Indonesia have used e-business including, websites, social media, e-commerce, and Enterprise Requirement Planning (ERP). The aspects that need to be considered include resource management, finance, procurement, logistics, to operational activities. In addition, the challenges that must be faced by MSMEs, in external conditions, must reduce the physical distance to cope with the spread of Covid-19. Due to the outbreak, MSMEs have been compelled to employ alternative methods that must be created and implemented to keep business processes functioning. Therefore, what factors can affect the acceptance of technology that is perceived by MSME owners to adjust their business needs. This research aims to modify TAM for e-business users, especially in MSMEs, to analyze the factors affecting the technology adoption process. The research method used is to build models and indicators from previous studies. However, as discussed in model development, three external variables were added: perceived cost, perceived risk, and facilitating conditions. The next stage is to conduct empirical research using a google form for MSME owners. Based on this framework, we propose a model for research propositions and contributions to scientific studies.